Redesain Panti Sosial Tresna Werdha Khusnul Khotimah Pekanbaru Dengan Pendekatan Caring Environment - Putri, Agnes Prameswari; Firzal, Yohannes; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Khusnul Khotimah Sosial Care Pekannaru is the only state-owned nursing home in Pekanbaru City, but with the increasing number of displaced elderly people, this nursing home can no longer accommodate elderly people. Besides capacity, design adjustments to the condition of the elderly must be done to create a conducive living community for the elderly themselves, this is because the elderly no longer have physical or mental stability. In this regard, the research methods used conducted to collect field data, literatures, and empirical studies. This redesign attempt has shown how the elderly must be cared for, shape behavior of elderly and the design that still adapts to the condition of the elderly. The results confirm that the principles of Caring Environment can be more appropriate in design for the elderly.Keyword: Caring Environment, Redesign, Nursing Home, Social Care